Persepsi Merek Dan Kualitas Layanan Pelanggan Kentucky Fried Chicken (KFC) - Delfi Anggreyani; Indah Chairunnisa; Mohamad Zein Saleh (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This research uses qualitative methodology to analyze brand perception and customer service quality at Kentucky Fried Chicken (KFC) restaurants. A literature review was used to obtain data. The results of this study show that KFC's brand image, particularly with regard to the taste and quality of its products, can influence the way customers perceive the restaurant. Customers also value responsiveness and consistency in service quality to have a positive experience. Without using direct interviews, this research provides in-depth insight into the things that influence customer impressions of service quality conditions at Kentucky Fried Chicken (KFC), knowing the effect of brand perception and service quality and on company sustainability on KFC, and this research can be used for marketing plans for the fast food industry and the growth of new companies. The objectives of this study are: to determine the condition of brand perception at Kentucky Fried Chicken (KFC), knowing Kentucky Fried Chicken (KFC).